Analisis Pengaruh Motivasi Konsumen dan Sikap Konsumen Terhadap Keputusan Pembelian Pupuk Phonska (Studi di Kabupaten Mojokerto) - Ajeng Lailil Ismiar Rosida (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
This study aims to analyze the influence of Consumer Motivation and Consumer Attitudes on purchasing decisions Phonska fertilizer PT. Petrokimia Gresik in Mojokerto. To find out how much influence the dependent variable (buying decisions) to the independent variables (Consumer Motivation and Consumer Attitudes) used regression analysis with analytical methods test t and f. This study uses a sample of 105 farmer that use Phonska Phonska fertilizer PT. Petrokimia Gresik . While sampling using purposive sampling techniques. The results of studies using multiple linear regression analysis, showed that simultaneous variable Consumer Motivation (X1) and Consumer Attitudes (X2) has a significant influence on buying decisions (Y). While partial, variable Consumer Motivation and Consumer Attitude showed a significant effect on decision buying consumen. Keyword : Consumer Motivation, Consumer Attitudes, Decision Buying